Organofunctionalisation of Polyoxometalates for Photocatalysis - Tsang, Nicole (2024)
The organofunctionalisation of polyoxometalates (POMs) has emerged as a powerful strategy for enhancing the diversity of POM clusters, resulting in structures with tuneable electrochemical and photochemical properties. Despite notable progress, the integration of these functionalised POMs into organic photocatalysis remains limited. The work presented in this thesis aims to advance the scope of functionalised POMs beyond the current state-of-theart and to gain a greater understanding of how structural variations influence the photochemical properties of POMs.